The Bolshevik revolution 1917-1918 : documents and materials - by James Bunyan and H. H. Fisher. (Stanford University Press)
"A reprint ... in which a few errata have been corrected and a few easily ascertained death dates added to the index.""This volume follows chronologically the Documents of Russian history, 1914-1917, published by the late Professor Frank A. Golder ... A considerable number of the documents of the present volume were selected and translated by Mr. Golder."